Pathogenic features of angiotensin II and BNP content in the nucleus of the solitary tract with etiological different arterial hypertension - Shiryayeva, A.; Danukalo, M.; Ширяєва, Анастасія Олегівна; Данукало, Максим Вікторович (Запорізький державний медичний університет, 2019)
Background. The nucleus of the solitary tract (NTS) is a primary brainstem structure, which accept incoming impulses from the chemo- and baroreceptors of the aortic arc. NTS is able to change the tone of other brain nuclei, that will anyway alter the activity of the sympathetic part of the autonomic nervous system and the level of blood pressure subsequently. According to modern data, some hormone-like substances are able to stimulate the activity of the neurons like classical neurotransmitters due to their local synthesis or inter-neuronal transport. Angiotensin II and brain natriuretic peptide (BNP) are actively studied today. Therefore, the aim of our work was to provide a characteristic of angiotensin II and BNP expression pattern in structure of the nucleus of the solitary tract with etiological different arterial hypertension. Materials and methods: research was conducted on 10 Wistar line rats, (control group) and 10 spontaneously hypertensive rats (SHR) which are the model of human essential hypertension. We also modeled endocrine-salt hypertension (ESAH). ESAH was induced by intraperitoneal injection of prednisolone (twice a day for 30 days: at 7 am - 2 mg/kg, at 20 pm - 4 mg/kg) with 5 ml of 2,3% NaCl solution forced intake. Blood pressure of the control group was 110/75 ± 5 mm Hg, while in ESAH rats was 155/90 ± 5 mm Hg and in SHR was 165/100 ± 10 mm Hg. For better detection of neuropeptides, colchicine was injected into the lateral ventricle of the rat’s brain in vivo. After the appropriate immunohistochemical treatment of the rat’s brain sections at the level of NTS, the following parameters were investigated: relative area of the immunoreactive material (IRM), IRM concentration and IRM content to the studied neuropeptides. All the data were processed by statistical methods.
Keywords: тези доповідей